Relasi religiusitas dengan kesepian pada remaja Etnis Tionghoa: The relationship between religiosity and loneliness in ethnic Chinese adolescents - Fitrie Aryani; Emmanuel Satyo Yuwono (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2024)
This research aimed to explore the relationship between religiosity and loneliness in ethnic Chinese adolescents. A total of 116 participants were involved in this research, who were selected using incidental sampling techniques. Data was collected using the Centrality of Religiosity Scale (CRS-15) developed by Huber and Huber and the UCLA Loneliness Scale created by Russell. Data were analyzed using the Pearson product moment correlation technique. The results of the analysis show a correlation coefficient of r = -0.112 and a significance value of 0.230 (p>0.05), which indicates a negative but not significant relationship between religiosity and loneliness in ethnic Chinese adolescents. This means, the higher the religiosity of ethnic Chinese teenagers, the lower their tendency to feel lonely. It is also said that the lower the religiosity, the higher their tendency to experience feelings of loneliness.